Art in Professional Training in Primary Education: Assessment and Curricular Challenges - Esquivel-Grados, José Theódulo; Venegas-Mejía, Valia; Altamirano-Julca, Yamandú; Altamirano-Sipán, Álvaro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The article is the product of a study with a mixed approach whose purpose was to analyze and understand the value of art in professional training in Education, based on the opinions of students, and the curricular challenges around art that innovations imply. The sample consisted of Primary Education students from a National University of Lima and to collect information on the appreciation of art in teacher training, a closed questionnaire of attitudes towards artistic expression activities in professional training in Education and for students was applied. curricular challenges an open questionnaire was administered. The results reflect a significant value assigned to art in teacher training and the need and importance of including art as a longitudinal area in the curriculum so that it contributes to the formation of artistic competences and soft skills of future teachers at the Education level. Primary, those that are essential in the teaching.